(untitled) (Scientific journal of the Fergana State University, 2023)
The article presents the information about the preparation of malt based on barley and wheat. The beneficial and healing sides of malt are illuminated. The chemical composition of wheat malt has been cited and information has been given about the food additives obtained on its basis. Food is treated with various chemicals that give a strong taste and aroma with the aim of prolonging shelf life, attracting and training people. As a result of food processing with such chemicals, various oncological, allergic and other chronic diseases are on the rise in the human body. With this, strong-acting antibiotics and other types of drugs are widely used in order to overcome such types of diseases